Successful and Reproducible Post-Operative Pain Control Using Multidisciplinary Opioid-Sparing Regimen in Patients Undergoing Left Ventricular Assist Device Implantation - Yaranov, Dmitry M.; Kendall, Kay; Miracle, Kimberly; Rosenquist, Richard; Jimenez, Xavier; Soltesz, Edward; Taylor, David O.; Tang, W.H. Wilson (Journal of cardiac failure, 2019)
Cardiac surgery is associated with significant acute pain. A proportion of patients will eventually transition to chronic pain, with possible ongoing use of opioids. Prescribers play consequential roles in achieving a balance between effective pain management and a patient's access to prolonged opioids. We developed an opioid-specific standards, an educational tool, and a patient agreement form. Mid-level providers completed a pain management course focused on the use of opioid alternatives. The aim of the present study was to investigate the effect of a multidisciplinary Opioid-Sparing Medical Regimen (OSMR) on pain levels and rate of opioid prescriptions upon discharge in patients undergoing left ventricular assist device (LVAD) implantation. A retrospective chart review of all patients receiving LVAD implant from January 1, 2014 to December 30, 2017 was performed. The study sample was limited to patients ≥18 years of age who underwent LVAD implantation. The intervention group consisted of subjects undergoing LVAD implantation, who received postoperative pain management using an OSMR after June 1, 2016. The comparison group consisted of subjects who received LVAD implant prior to OSMR implementation. The pain intensity was independently reported by patients to nursing staff and documented in the electronic medical record. The 11-point Numeric Rating Scale was utilized. A total of 194 patients met inclusion criteria. Comparison and OSMR groups represented 97 patients each. There was a reduction in the number of patients requiring opioid prescriptions at the time of hospital discharge following the implementation of an OSMR. Total opioid prescriptions upon discharge decreased from a quarterly average of 67% to 16%. Additionally, at 18 months following implementation of an OSMR, no opioid prescriptions were required at hospital discharge for the management of acute postoperative pain (Figure 1). There was no overall difference in reported pain scores between the 2 cohorts (Figure 2). No statistically significant difference was found on daily reported scores from the time of transfer out of the ICU to day 15. OSMR implementation for acute post-operative pain control in LVAD patients is effective and reproducible, with pain scores comparable to an opioid based medication regimen. OSMR was shown to minimize the need for discharge opioid prescriptions potentially reducing the risk of new persistent opioid use.